P-193 Deconstructing the silos: innovative commissioning of palliative care consultants within a local healthcare economy may improve co-ordinated whole person care for patients with generalist and specialist palliative care needs. Issue Volume 5: Issue (2015)Supplement 3 (1st November 2015) - Davis, Charlie; Lutyens, Joanna; Gillett, Janet; Leask, Catherine; Vijeratnam, Niranjali; Shorthose, Kate; Edwards, Simon; Lee, Ann
Abstract : Background: The 2008 Marie Curie Delivering Choice Programme described palliative care providers and processes within the county. The conclusions highlighted the need for consortium based commissioning of a specialist palliative medicine consultant group. Aim: Employ palliative care consultants to enhance person centred care via current teams. Indirectly improve care via mentoring and education of generalists. Facilitate the dissolution of 'care silos'. Contribute to integrated care. Services and developments must benefit patients. Approach used: NHS Somerset Clinical Commissioning Group collaborated with public and independent organisations to fund and employ medical consultants. The consortium includes hospice inpatient units, acute trusts and specialist palliative care community teams. Posts are hosted by the community trust which includes district nursing and 13 community hospitals. Outcomes: Novel placement of consultants within multi-professional partnerships enhances person-centred care via consultant availability to specialist nurses caring for patients across 2 hospice in-patient units, specialist palliative community patients and over 1000 acute medical and surgical beds over 2 trusts. This is in addition to in and out-of-hours support for generalist colleagues via a 24/7 advice line. Conclusions: The consultant group directly and indirectly influence care within all contexts of a patient's journey. Challenges in this collaborative approach are overcome with a shared vision of patient care on a continuum, irrespective of place or time. Enriched experience and collective skill-set of senior medical staff compared to single-organisation funded posts. Patient focussed palliative care consortiums within health economies can develop an awareness of needs for both service provision and strategic planning through broad connexions within the locality. Catalysing multi-professional dialogue can enhance patient choice in place-of-care. Application to hospice practice: Hospice can enhance care through consortium funding. Varied insight into local palliative healthcare economy enhances development and delivery of co-ordinated whole person careto a greater extent than solely hospice employed consultants.